2019
DOI: 10.15171/ijhpm.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Translating Allied Health Knowledge (TAHK) Framework

Abstract: Background: While evidence-based practice is a familiar concept to allied health clinicians, knowledge translation (KT) is less well known and understood. The need for a framework that enables allied health clinicians to access and engage with KT was identified. The aim of this paper is to describe the development of the Translating Allied Health Knowledge (TAHK) Framework. Methods: An iterative and collaborative process involving clinician and academic knowledge partners was utilised to develop the TAHK Fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Medical staff (and nursing staff) were gatekeepers for this service, as they triaged and determined whether appropriate patients were referred for assessment and treatment. This is a common feature of the allied health practice context, and demands multidisciplinary collaboration which adds to the complexity of implementation of every innovation (30). The ndings of this study indicated these relationships were successfully negotiated during this implementation process.…”
Section: Discussionmentioning
confidence: 70%
“…Medical staff (and nursing staff) were gatekeepers for this service, as they triaged and determined whether appropriate patients were referred for assessment and treatment. This is a common feature of the allied health practice context, and demands multidisciplinary collaboration which adds to the complexity of implementation of every innovation (30). The ndings of this study indicated these relationships were successfully negotiated during this implementation process.…”
Section: Discussionmentioning
confidence: 70%
“…The shift in qualitative data to 'external' sources of support in the second survey may indicate that the strategy was meeting needs more effectively at the organizational level, but could not meet all of The multidimensional workplace strategy implemented in this study directly addressed several of the determinants known to increase the effectiveness of allied health knowledge translation (49). The strategy was aligned with organizational systems (such as supervision) which helped to embed it into practice, and leadership structures at multiple levels of the organization were utilized to drive and maintain momentum, particularly in regards to cultural changes.…”
Section: Discussionmentioning
confidence: 92%
“…The focus on skin and wound care, and nutrition found in the literature review as not as prominent in the participants perceptions, but were mentioned in passing. Given the influence of contextual factors on implementation in healthcare (44), some variation in focus and priority is expected between healthcare organisations and systems, but does pose a challenge to the development of generalised models of care. Many examples of multidisciplinary approaches to the care of people with obesity are available in the literature (9,26-28), although few have been evaluated for their ability to enable patients to receive a personalized package of care that meets their specific constellation of needs.…”
Section: Discussionmentioning
confidence: 99%